Pengelolaan Krisis Pangan di Kampung Wih Bersih dan Peran Administrasi Negara dan Komunikasi Krisis dalam Menangani Kelangkaan Pangan - Harahap, Viana Safrida; Micer, Ihwan Bil; Rizki, Putri (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Food scarcity is one of the problems faced by many cities around the world. Indonesian is the fourth most populous country in the world after China, India and the United States with 237.6 million people in 2010 (Population Census, 2010). This significant increase in population has caused food availability in the world, including Indonesia, to become increasingly scarce and it is not surprising that the world, one of which is Indonesia, will experience a food crisis and result in the danger of hunger lurking throughout the world. country. Indonesia is experiencing a food crisis that is quite worrying. It is estimated that 179 to 181 million people in 41 countries will face a food crisis. This research explores the role of state administration and crisis communication in handling the food crisis in Kampung Wih Bersih. The focus is on appropriate inter-agency coordination, policies and communication efforts to address food scarcity. Through case analysis, this research highlights the importance of careful planning, effective coordination, and clear communication in crisis management. Recommendations are provided to strengthen state administrative capacity and expand crisis communication strategies to maintain food security in rural areas. This activity was held on Friday 19 October 2023. Before the activity started, the KKNT group held a discussion regarding activity partners, learning materials regarding food Scarcity in the Wih Bersih village community.